Association between longitudinal blood pressure and prognosis after treatment of cerebral aneurysm: A nationwide population-based cohort study. - Jinkwon Kim (Public Library of Science (PLoS), 2021)
Background High blood pressure is a major risk factor for the development and rupture of cerebral aneurysm. Endovascular coil embolization and surgical clipping are established procedures to treat cerebral aneurysm. However, longitudinal data of blood pressure after the treatment of cerebral aneurysm and its impact on long-term prognosis are not well known. Methods This retrospective cohort study included 1275 patients who underwent endovascular coil embolization (n = 558) or surgical clipping (n = 717) of cerebral aneurysm in 2002-2015 using the nationwide health screening database of Korea. Systolic and diastolic blood pressure of patients were repeatedly obtained from the nationwide health screening program. We performed a multivariate time-dependent Cox regression analysis of the primary composite outcome of stroke, myocardial infarction, and all-cause death. Results During the mean follow-up period of 6.13 ± 3.41 years, 89 patients suffered the primary outcome. Among the total 3546 times of blood pressure measurement, uncontrolled high blood pressure (systolic ≥140 mmHg or diastolic ≥90 mmHg) was 22.9%. There was a significantly increased risk of primary outcome with high systolic (adjusted HR [95% CI] per 10 mmHg, 1.16 [1.01-1.35]) and diastolic (adjusted HR [95% CI] per 10 mmHg, 1.32 [1.06-1.64]) blood pressure. Conclusions High blood pressure is prevalent even in patients who received treatment for cerebral aneurysm, which is significantly associated with poor outcome. Strict control of high blood pressure may further improve the prognosis of patients with cerebral aneurysm.